Injury rate and injury pattern among elite world cup snowboarders: a 6-year cohort study - Major, D.; Steenstrup, S. E.; Bere, T.; Bahr, R.; Nordsletten, L. (British Journal of Sports Medicine, 2014)
Background: There is limited knowledge on the injury rate and injury pattern in the different disciplines among elite snowboarders. Objective: The aim of this study was to describe and compare the injury rate and injury pattern among the different International Ski Federation (Fédération Internationale de Ski, FIS) World Cup (WC) snowboard disciplines. Methods: We conducted retrospective interviews with FIS WC snowboard athletes at the end of each season in the period 2007-2012, to register all acute injuries sustained during training or competition during the competitive season requiring attention by medical personnel. To calculate the exposure, we obtained information from result lists from the FIS competition database for all WC competitions for each of the interviewed athletes. Results: We registered a total of 574 injuries among 1432 athletes, accounting for an overall injury rate of 40.1 injuries/100 athlete/season. A total of 171 injuries occurred during the FIS WC competitions, corresponding to 6.4 injuries/1000 runs. During competition, injury risk was highest in snowboard cross with 11.9/1000 runs, followed by 6.3 in halfpipe, 3.6 in big air and 2.8 in parallel giant slalom/parallel slalom (PGS/PSL). Snowboard cross also had the highest risk of severe injuries (>28 days absence). No differences in injury risk were detected between male and female snowboarders. The most commonly injured body part was the knee (17.8%), followed by the shoulder/clavicle (13.4%) and head/face (13.2%). The risk of knee injury (the most common injury type) and head injury was significantly higher in snowboard cross and halfpipe compared to PGS/PSL. Conclusions: The risk of injuries was higher in snowboard cross than in halfpipe, big air and PGS/PSL. The most commonly injured body part was the knee. Prevention of snowboard injuries among elite snowboarders should focus on knee injuries, severe injuries and snowboard cross athletes.